Analysis of Andisol Soil Quality Index in Scallion (Allium fistulosum L.) Agricultural Land in Tosari District, Pasuruan Regency - Salamah, Mahmudatu Fais; Arifin, A. Zainul; Purnamasari, Retno Tri; Hidayanto, Fajar (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2024)
Soil quality assessment can be done by monitoring the dynamic conditions of various indicators that influence it. Measuring these indicators produces a soil quality index (IKT), which is a tool to evaluate the impact of land management practices (Mas'udi et al., 2021). This research aims to determine the distribution of the soil quality index on shallot (Allium fistulosum L) agricultural land in Tosari sub-district, Pasuruan district, East Java. The research was carried out in Tosari sub-district, Pasuruan district at an altitude of 1700 meters above sea level. In September 2023 – January 2024. This research uses a purposive sampling method for taking soil samples. Next, it was analyzed in the laboratory for texture, volume weight, porosity, C-organic, pH, P-available, K-exchangeable and the rooting depth was measured. The soil quality index is calculated using the criteria of Mausbach and Seybold (1998), which can be adjusted to field conditions using the Minimum Data Set (MDS). Based on the research results, it shows that there are differences in the Soil Quality Index on Onion Leaf land in several villages in Tosari sub-district. Leek fields in Tosari sub-district have two criteria, namely medium and good criteria. Tosari Village, Ngawidono Village, Mororejo Village and Kandangan Village are classified as Good (B) while Podokoyo Village is classified as Medium (S).